Prevalence of Coxiella burnetii seropositivity and shedding in farm, pet and feral cats and associated risk factors in farm cats in Quebec, Canada. (15th February 2021) - Cyr, J.; Turcotte, M.-È.; Desrosiers, A.; Bélanger, D.; Harel, J.; Tremblay, D.; Leboeuf, A.; Gagnon, C. A.; Côté, J.-C.; Arsenault, J.
Abstract: Cats represent a potential source of Coxiella burnetii, the aetiological agent of Q fever in humans. The prevalence and risk factors of C. burnetii infection in farm, pet and feral cats were studied in Quebec, Canada, using a cross-sectional study. Serum samples were tested using a specific enzyme-linked immunosorbent assay (ELISA) for the presence of antibodies against C. burnetii, whereas rectal swabs were assayed using real-time quantitative polymerase chain reaction (qPCR) for the molecular detection of the bacteria. Potential risk factors for farm cats were investigated using clinical examinations, questionnaires and results from a concurrent study on C. burnetii farm status. A total of 184 cats were tested: 59 from ruminant farms, 73 pets and 52 feral cats. Among farm cats, 2/59 (3.4%) were ELISA-positive, 3/59 (5.1%) were ELISA-doubtful and 1/59 (1.7%) was qPCR-positive. All pets and feral cats were negative to C. burnetii ELISA and qPCR. Farm cat positivity was associated with a positive C. burnetii status on the ruminant farm (prevalence ratio = 7.6, P = 0.03). Our results suggest that although pet and feral cats do not seem to pose a great C. burnetii risk to public health, more active care should be taken when in contact with cats from ruminant farms.